Exposure to stressors and antimicrobials induces cell-autonomous ultrastructural heterogeneity of an intracellular bacterial pathogen - Schulte, Marc; Hensel, Michael; Miskiewicz, Katarzyna (Frontiers in Cellular and Infection Microbiology, 2022)
Despite their clonality, intracellular bacterial pathogens commonly show remarkable physiological heterogeneity during infection of host cells. Physiological heterogeneity results in distinct ultrastructural morphotypes, but the correlation between bacterial physiological state and ultrastructural appearance remains to be established. In this study, we showed that individual cells of Salmonella enterica serovar Typhimurium are heterogeneous in their ultrastructure. Two morphotypes based on the criterion of cytoplasmic density were discriminated after growth under standard culture conditions, as well as during intracellular lifestyle in mammalian host cells. We identified environmental conditions which affect cytoplasmic densities. Using compounds generating oxygen radicals and defined mutant strains, we were able to link the occurrence of an electron-dense ultrastructural morphotype to exposure to oxidative stress and other stressors. Furthermore, by combining ultrastructural analyses of Salmonella during infection and fluorescence reporter analyses for cell viability, we provided evidence that two characterized ultrastructural morphotypes with electron-lucent or electron-dense cytoplasm represent viable cells. Moreover, the presence of electron-dense types is stress related and can be experimentally induced only when amino acids are available in the medium. Our study proposes ultrastructural morphotypes as marker for physiological states of individual intracellular pathogens providing a new marker for single cell analyses.